Natural drying methods to promote fuel quality enhancement of small energywood stems - Röser, Dominik; Erkkilä, Ari; Mola-Yudego, Blas; Sikanen, Lauri; Prinz, Robert; Heikkinen, Antti; Kaipainen, Heikki; Oravainen, Heikki; Hillebrand, Kari; Emer, Beatrice; Väätainen, Kari (Finnish Forest Research Institute, 2010)
Due to fluctuating fossil fuel prices the use of forest biomass for energy is expected to increase considerably in the future. Today, the demand for high quality wood fuel products such as chopped firewood or pellets has increased price pressure on these products. In order to make the production more cost-effective new methods to optimize their production have to be found. Drying of raw material in the forest in order to improve the quality of the raw material and to reduce transportation costs can considerably improve the overall efficiency of the supply chain. It also enables longer storing periods and decreases GHG emissions and dry matter losses during storing. The purpose of the study was to test natural drying and the effect of different degrees of partial debarking and different methods of bark scarifying as well as covering on natural drying of energywood stems. The test included laboratory tests in Finland and field trials in Finland, Scotland and Italy, using local practices and forest species commonly used as a raw material for different forest energy products. In the laboratory test for birch, partial debarking and scarifying can be as effective drying accelerants as traditional splitting. It is important that scarifying is done all over the stem. During the test, untreated stems were drying from original 48% of moisture down to 35% during 6 months of drying between March and September. During the same period, split, partially debarked and scarified stems achieved more than 10%-units lover moisture. With pine, scarifying does not work as effectively with small percentages of removed or scarified bark.According to the results of the field trials, the debarking using a harvester head had a significant effect on moisture content decrease during the drying season especially when the stacks were covered. Covering is more vital in rainier circumstanses, but nevertheless there are also notable differences between tree species. The results show that the tested broad-leaved trees, (Petula pubescens), alder (Alnus incana) and sitka spruce (Picea sitchensis) dry faster than pine (Pinus sylvestris) and lodge pole pine (Pinus contorta).The results showed that debarking using, e.g. a harvester head, can be quite demanding due to different characteristics of tree species and diameters. The debarking device should be designed so that it could be switched on only when needed. This would ensure that the harvester head could be used to harvest normal timber and also energy wood. In conclusion, the drying season is essential to decrease the moisture content particularly in Finland and Scotland. The results show that the moisture content can be decreased by 15 20% in several months using only solar and wind power if more bark than normal is removed and the piles are covered.
Keywords: metsäenergia; moisture content; natural drying; wood-fuel logistics